Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1109/jtehm.2013.2277870
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Innovative In-Ear Pulse Oximetry for Unobtrusive Cardiovascular and Pulmonary Monitoring During Sleep

Abstract: Homecare is healthcare based on the principle “outpatient before inpatient,” with the aim of moving at least some care-delivery to the home. But reliable determination of vital signs at home requires new, smart sensors, which can be used by the patients themselves. We present a novel pulse oximetry sensor worn in the ear channel. It was previously shown that measurement of heart rate, arterial oxygen saturation and related respiratory information can be performed with reliable accuracy under laboratory conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 16 publications
(24 reference statements)
0
27
0
Order By: Relevance
“…In parallel with data fusion and sensor technologies, smart sensors have also been widely used in biomedical applications to acquire and process data to be used in assisting with diagnosis , self-diagnosis [111], telemedicine [112], home monitoring (home care) [113], and to save lives [114]. In the construction of these sensors, some electronics principles and/or physicochemical reactions, such as biosensors, are noticeable.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…In parallel with data fusion and sensor technologies, smart sensors have also been widely used in biomedical applications to acquire and process data to be used in assisting with diagnosis , self-diagnosis [111], telemedicine [112], home monitoring (home care) [113], and to save lives [114]. In the construction of these sensors, some electronics principles and/or physicochemical reactions, such as biosensors, are noticeable.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…In [50], an experiment is designed to check the signal quality from a different part of the In [51], an in-ear reflectance sensor is designed for measuring cardiovascular signals during sleep based on a clinical study. The designed sensor can simultaneously measure the heart rate, 2 and the respiration rate, and it might decrease the amount of required sensors, cables and other devices which improves the quality of the sleep during the examination.…”
Section: Sensor Placementmentioning
confidence: 99%
“…The reflective sensor element is placed at the inner tragus. The sensor is connected to the sensor interface device via a cable which is taped for artifact reduction[51].…”
mentioning
confidence: 99%
“…Because of these various limitations of different PPG sensors at various anatomical locations, many studies have been conducted exploring their accuracy under different conditions. Other studies have collectively compared PPG at the finger, forearm, earlobe, ear canal, wrist, shoulder, forehead, chest, temple, neck, rib cage, wrist, lower back, and tibia [12,[20][21][22][23][24][25]. The consensus was that the forehead and finger locations provide the most accurate PR and SpO 2 measurements in static conditions, although both were found to be susceptible to deleterious effects from varying dynamic conditions, especially movement and desaturation events.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, in another study by Ross et al comparing PPG sensors at high altitudes at the finger, forehead, and ear lobe, gold standard arterial blood gas results revealed the finger location to perform best, followed by the earlobe location and finally the forehead with the lowest performance for detecting hypoxia [23]. Studies investigating the in-ear location for PPG sensors have found this location to be sufficiently accurate for detecting heart rate and oxygen saturation levels relative to the finger location and advantageous as a centrally located PPG sensor site [21,25,27]. However, a study by Passler et al determined that motion artifact due to normal jaw movements from chewing gum and talking throughout data recording had a significant deleterious influence on the in-ear location, resulting in a signal interference too intense to determine a precise pattern of pulse rate [28].…”
Section: Introductionmentioning
confidence: 99%